2018
DOI: 10.1371/journal.pone.0190405
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural patterns only predict concurrent BMI status and not BMI trajectories in a sample of youth in Ontario, Canada

Abstract: BackgroundYouth are engaging in multiple risky behaviours, increasing their risk of overweight, obesity, and related chronic diseases. The objective of this study was to examine the effect of engaging in unique clusters of unhealthy behaviours on youths’ body mass index (BMI) trajectories.MethodsThis study used a linked-longitudinal sample of Grades 9 and 10 students (13 to 17 years of age) participating in the COMPASS host study. Students reported obesity-related and other risky behaviours at baseline and hei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(50 citation statements)
references
References 55 publications
1
44
0
5
Order By: Relevance
“…TV viewing, video games). 37 Consistent with earlier research, 5,6 our analyses indicate that there are annual increases in BMI across genders but that the predictors of the annual increase differ. Physical activity and substance use are not likely predictors of increasing BMI in females.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…TV viewing, video games). 37 Consistent with earlier research, 5,6 our analyses indicate that there are annual increases in BMI across genders but that the predictors of the annual increase differ. Physical activity and substance use are not likely predictors of increasing BMI in females.…”
Section: Discussionsupporting
confidence: 88%
“…Similar studies that only adjusted for gender might have not found any association because they did not stratify by gender. 6 In addition, we accounted for monotone type missingness by using maximum likelihood models, based on the assumption that data are missing at random. These models are preferable over those that are based on complete case analysis because the latter assume the outcome is missing entirely at random.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations